Analisis Tingkat Kesehatan Bank Umum BUMN Yang Masuk Dalam Top 1000 World Banks 2024 Versi The Banker Menggunakan Metode RGEC - Zalukhu, Rika Surianto; Hutauruk, Rapat Piter Sony; Collyn, Daniel; Hutabarat, Metyria Imelda (Accounting Progress, 2025)
This study aims to analyze the financial health of state-owned commercial banks (Bank Umum BUMN) included in the Top 1000 World Banks 2024 list by The Banker using the RGEC approach (Risk Profile, Good Corporate Governance, Earnings, and Capital). This is a descriptive quantitative study utilizing secondary data in the form of annual reports from 2021 to 2023, obtained from the official websites of the Indonesia Stock Exchange (IDX) and each respective bank. The risk profile aspect was assessed using the Non-Performing Loan (NPL) ratio, good corporate governance was evaluated based on the self-assessment results of each bank, earnings were analyzed through Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM), while capital was measured using the Capital Adequacy Ratio (CAR). The results showed that during the 2021–2023 period, the four state-owned commercial banks achieved Composite Rating 1 (PK-1), indicating a "very healthy" status. The risk profile and GCG were in the “healthy” category, while the earnings and capital aspects were in the “very healthy” category with positive growth trends, particularly in ROA, ROE, and NIM. These findings indicate that, overall, state-owned commercial banks maintain strong financial performance and health, although there is still room for improvement in risk and governance aspects to align with other financial indicators. This study contributes to stakeholders’ understanding of the stability and long-term sustainability prospects of state-owned banks.